Twofish cryptographic APPLICATION FOR SAFETY DATA COMPUTER - Marzuki Marzuki Marzuki (Majalah SIKOMTEK, 2005)
Twofish is a 128-bit block cipher that can accept variable length keys up to 256 bits. Cipheris a 16 round Feistel network with a bijective F function consists of four key-dependent 8-by-8-bit S-Box, a constant of 4-by-four as the maximum distance to the reference matrix areseparated on GF teripisah ( 28), a "pseudo-Hadamard transformation, according to the roundbit, and a key schedule that is designed carefully. Twofish can be implemented in hardwarewith 14 000 gates. The design works for both rounds of the key schedule permits a widetradeoff between speed, software size, setting time, the composition of the gates, andmemory. Kriptanalisis Twofish has extensive property, ie attacks can be solved in five roundswith 222.5 plaintexts and 251 effort choices.